Approach to mitigate the initial complexity of software maintenance based on Clean Architecture - Ricse, Anthony (2025)
Initial maintainability in software systems using Clean Architecture presents challenges, especially in small projects. This is due to the framework's approach focused on long-term sustainability. This leads to low stability and difficult analyzability, creating an obstacle for integrating new requirements, and consequently increasing development effort and costs. The present research proposes a simplified 3-layer Clean Architecture to reduce the initial maintenance complexity observed in traditional 4-layer systems. The proposed methodology encompassed four key phases: (i) Business entity planning, (ii) Architecture design (layers, communication, and technology), system implementation, and proposal validation comparing experimental 3-layer with control 4-layer groups. The results, evaluated according to ISO/IEC 25010, indicated that Clean Architecture for small projects decreased maintainability: modularity by 1.28%, reusability by 4.27%, analysis by 0.11%, modification by 0.42% and capacity to be tested or testability by 4.29%. This suggests that the simplified architectural approach reduce initial maintenance challenges.